OPTIMIZING STUDENT'S UNDERSTANDING THROUGH THE USE OF OSH LAND MEASUREMENT GUIDELINES IN VOCATIONAL HIGH SCHOOL - Muhammad Nur Fuad; Rini Kusumawardani; Eko Supraptono (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Occupational Safety and Health (OSH) is essential in every field of work, especially in the construction sector, which has a high risk. One way to improve understanding of OSH is through learning when students carryout practices in vocational schools. This study aims to determine the extent of optimization of students’ understanding through the use of OSH guidelines and evaluate the extent to which the use of OSHguidelines can improve student understanding. The study used a quantitative approach with a pretest and post-test design. This study involved 35 students as samples, namely students of class X TKP 2 of SMK Negeri 3 Semarang. The results showed that applying the OSH guide significantly improved students’ understanding, with an average pretest score of 62.77 and a post-test of 92.06. The Paired Samples T-Test test yielded a p-value of 0.000, indicating a significant difference between the pretest and post-test scores. The ANOVA test results also indicated that students’ response to the OSH guide significantly affected their improved  understanding. These findings indicate that using OSH guidelines in learning land measurement practices effectively improvesstudents’ understanding and awareness of the importance of safety in the field.